Mechanical response and equilibrium swelling of temperature-responsive gels. (September 2017) - Drozdov, A.D.; deClaville Christiansen, J.
Graphical abstract: Highlights: A model is developed for the mechanical response of temperature-sensitive gels. Constitutive equations account for the growth of elastic moduli under phase separation. Material parameters are found by fitting swelling diagrams on several gels. Simulation confirms the ability to predict observations in mechanical tests. Abstract: A model is developed for the mechanical behavior of thermo-responsive gels that accounts for an increase in concentration of physical cross-links between chains driven by phase separation. Governing equations are derived for equilibrium water uptake under unconstrained and constrained swelling, as well as for the elastic response of swollen gels. These relations are applied to the analysis of swelling diagrams on NIPA, VCL, PEG, and NIPA-DMIAA gels. The ability of the model to predict the growth of elastic moduli above the volume phase transition temperature is confirmed by numerical simulation.